2020
DOI: 10.1063/5.0013487
|View full text |Cite
|
Sign up to set email alerts
|

Comparative studies on ferroelectric switching kinetics of sputtered Hf0.5Zr0.5O2 thin films with variations in film thickness and crystallinity

Abstract: Ferroelectric Hf0.5Zr0.5O2 (HZO) thin film capacitors with Pt/HZO/TiN structures were characterized to investigate the effects of oxygen partial pressure (PO2) and film thickness on the ferroelectric properties and switching dynamics of sputter-deposited HZO thin films. The PO2 during deposition and the film thickness varied from 0% to 1.5% and from 20 to 30 nm, respectively. The ferroelectric remnant polarization (2Pr) was 24.8 μC/cm2 for the 20-nm-thick HZO thin film deposited at a PO2 of 0% and decreased wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(18 citation statements)
references
References 46 publications
0
18
0
Order By: Relevance
“…Findings were analogous in Hf 0.5 Zr 0.5 O 2 films deposited via physical vapour deposition, as in the case of Lee et al 48 and Ryu et al 49 Both groups demonstrated that increasing oxygen partial pressure during deposition suppresses the ferroelectric properties in the layers and again favours the stabilization of the m-phase. Since PVD layers are most likely free of carbon contaminants, the stabilization of the ferroelectric phase together with the increase in leakage current led them to conclude that V O are generated in the films for low oxygen supply.…”
Section: Doped Hfomentioning
confidence: 56%
See 2 more Smart Citations
“…Findings were analogous in Hf 0.5 Zr 0.5 O 2 films deposited via physical vapour deposition, as in the case of Lee et al 48 and Ryu et al 49 Both groups demonstrated that increasing oxygen partial pressure during deposition suppresses the ferroelectric properties in the layers and again favours the stabilization of the m-phase. Since PVD layers are most likely free of carbon contaminants, the stabilization of the ferroelectric phase together with the increase in leakage current led them to conclude that V O are generated in the films for low oxygen supply.…”
Section: Doped Hfomentioning
confidence: 56%
“…87,88 Recently, switching kinetics started to be addressed by more research groups and some studies looked at how the switching behaviour can be affected from the oxygen content in the examined layers. As an example, Ryu et al 49 studied the switching of PVD grown Hf 0.5 Zr 0.5 O 2 thin films when varying the oxygen partial pressure from 0 to 1%. By means of the nucleation limited switching model, they calculated an increasing activation energy (E act ) for increasing oxygen content.…”
Section: Fecap Performance and Reliabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the ferroelectric polarization switching characteristics are critically determined by the relative amounts of various crystalline phases included within the FLs, 55 which are significantly influenced by such process parameters as the types of adjacent layers underneath the FL and atomic compositions of the FLs. Thus, as a second concern, the variations in the crystallinity and crystalline phases of the FLs were examined in terms of important control parameters to improve the device operations of MFIS capacitors.…”
Section: Resultsmentioning
confidence: 99%
“…The switching times in HZO films of different thicknesses prepared under different O 2 pressure were investigated by Ryu et al [ 87 ] A comparative study based on KAI and NLS switching models showed that NLS model can provide better fitting over the full range of polarization switching. The switching times could be modulated from 0.46 to 1.58 μs by varying the partial O 2 pressure during deposition and film thickness.…”
Section: Origin Of Ferroelectricity and Domain Dynamicsmentioning
confidence: 99%